Quality assurance management - Fox, Michael J. (London ; New York : Chapman and Hall, 1993)
This book is divided into four parts: What managing quality means; Quality assurance techniques; Using people effectively; and Quality - the key to prosperity.
Keywords: Management; Assurance; Quality assurance -- Management